Strengthening Community Through Women's Participation in Common Pots. - (:unkn) unknown (My University, 2026)
Common pots are organizations led by women from the most vulnerable neighborhoods of Peru's main cities that collectively prepare meals for their families. Although they have a long history dating back to the late 1970s (Blondet and Montero, 1995), the ec